2011
DOI: 10.1016/j.jval.2011.08.860
|View full text |Cite
|
Sign up to set email alerts
|

PCV141 Current Management Pathway of Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention in Greece. Results from Aptorii Study

Abstract: 2,800USD), non-fatal IS with total disability 6,280BRL (3,934USD), embolism 11,810BRL (7,398 USD), transient ischemic attack 1,808BRL (1,133USD), fatal intracranial hemorrhage 15,572BRL (9,754USD), fatal hemorrhagic stroke (HE) 23,260BRL (14,570USD), non-fatal HE without disability 2,812BRL (1,761USD), non-fatal HE with moderate disability 4,470BRL (2,800USD), non-fatal HE with total disability 6,280BRL (3,934USD), fatal extracranial hemorrhage 1,018BRL (638USD), minor bleed 19BRL (12USD), fatal acute myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This limitation meant that it was not possible to explore some of the other known factors that could affect the QOL in patients with ACS such as physical activity, central obesity, education, and smoking [14][15][16], which were not available in the data set. Also, the number of subjects included was relatively small compared with the sample sizes of other studies [14,15,20]. Other limitations were that the small sample at baseline was compounded by the loss of subjects during follow-up such that only 53 subjects were available for analysis at 12 months post-ACS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation meant that it was not possible to explore some of the other known factors that could affect the QOL in patients with ACS such as physical activity, central obesity, education, and smoking [14][15][16], which were not available in the data set. Also, the number of subjects included was relatively small compared with the sample sizes of other studies [14,15,20]. Other limitations were that the small sample at baseline was compounded by the loss of subjects during follow-up such that only 53 subjects were available for analysis at 12 months post-ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have reported QOL among patients with ACS are mostly from developed countries. Among the demographic and clinical factors that have been identified to have an impact were age [14,15], sex [14][15][16][17][18], a previous cardiovascular (CV) event [16,19], angina severity [16], type of ACS [18,20], depression [16,17,21], and physical functioning [15,18,19]. From Malaysia, a study by Chin et al [4] reported that patients' age, percutaneous coronary intervention (PCI), and fibrinolytic therapy were factors associated with patient mortality but did not report QOL-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…The antiplatelet treatment observational registry (APTOR II) study showed an improvement in QoL in patients treated with clopidogrel. A greater improvement was observed among the patients with STEMI 24 . Although these studies demonstrated that the use of clopidogrel improved the QoL, these studies did not evaluate the deterioration in QoL after discharge/withdrawal of therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Comparing ACS therapies and assessment of the impact of the disease on the patients requires accurate assessmentof quality of life (QOL) and symptom scales (3)(4)(5).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%